2020
DOI: 10.1111/1346-8138.15567
|View full text |Cite
|
Sign up to set email alerts
|

Skin manifestations in COVID‐19: The tropics experience

Abstract: Dear Editor, Reports concerning cutaneous manifestations in coronavirus disease 2019 (COVID-19) have been mostly from temperate regions, namely Western countries and China, with prevalence rates of 0.20-20.45%. 1 Information on other races, ethnicities and locales is lacking. Thailand is located in the tropical region; thus, we hypothesize that different patterns of skin manifestations may ensue. From 9 March to 18 April 2020, 187 patients with COVID-19 were diagnosed at King Chulalongkorn Memorial Hospital, B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 4 publications
1
11
0
1
Order By: Relevance
“…There were no cases with pseudo-chilblain or livedoid lesions, as reported in other regions, especially Europe [ 17 ]. Only urticaria and maculopapular rash were found in this study, which corresponds with the findings of other studies in tropical countries [ 18 , 19 ]. This might be explained by climate differences and/or a lower severity of COVID-19 infections.…”
Section: Discussionsupporting
confidence: 93%
“…There were no cases with pseudo-chilblain or livedoid lesions, as reported in other regions, especially Europe [ 17 ]. Only urticaria and maculopapular rash were found in this study, which corresponds with the findings of other studies in tropical countries [ 18 , 19 ]. This might be explained by climate differences and/or a lower severity of COVID-19 infections.…”
Section: Discussionsupporting
confidence: 93%
“…Two patients with diffuse vesicular eruption were reported in a French study involving both outpatients and inpatients 8 . Vesicular eruptions have been described also in Thailand, in 2 out of 153 patients diagnosed of COVID‐19 9 . A similar rash was described in one patient in Barcelona, whereas 2 out of 130 inpatients evaluated in a hospital in Rome showed herpetiform grouped vesicles.…”
Section: Resultsmentioning
confidence: 84%
“…The latter could have been caused, according to the authors, by human herpes virus 1 or 2 3 . Human herpes virus reactivation would not be surprising among critical inpatients; Hedou et al reported one in an intubated patient with SARS‐CoV‐2 infection, as well as Rerknimitr et al 9,10 A higher incidence of herpes zoster has also been reported 6 …”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Regarding skin lesions in COVID-19, there are various forms [3]. Sometimes, the lesions are missed diagnosed as other problem [4]. It is necessary that practitioner has to investigate for possible COVID-19 in any patients presenting with unexplained cutaneous lesions.…”
mentioning
confidence: 99%